Pathology and Pathogenesis of Progressive Multiple Sclerosis: Concepts and Controversies - Schumacher, Adrian-Minh; Mahler, Christoph; Kerschensteiner, Martin (Neurology International Open, 2017)
Multiple sclerosis (MS) is an inflammatory disease of the central nervous system that initially is often dominated by relapsing-remitting neurological symptoms. With increasing disease duration these relapses are more and more superimposed by a progressive disease process that leads to an irreversible accumulation of motor, sensory and cognitive deficits. This progressive phase of MS is still only incompletely understood and by and large refractory to therapy. Here we aim to use recent pathological and pathomechanistic insights to outline a unifying concept of progressive MS. Based on this view of the disease we examine current controversies surrounding progressive MS. We discuss whether neurodegenerative or inflammatory processes drive progression, question whether the classification of primary and secondary progressive MS is all that useful and deliberate, which therapeutic strategies are best suited to limit the insidious neurological decline of progressive MS patients.
Keywords: multiple sclerosis; white matter pathology; grey matter pathology; chronic inflammation; neurodegeneration